PD-L1 Expression Is an Independent Marker for Lymph Node Metastasis in Middle Eastern Endometrial Cancer - Abdul K. Siraj; Sandeep Kumar Parvathareddy; Padmanaban Annaiyappanaidu; Nabil Siraj; Maha Al-Rasheed; Ismail A. Al-Badawi; Fouad Al-Dayel; Khawla S. Al-Kuraya (Diagnostics, 2021)
Programmed death ligand 1 (PD-L1) expression in endometrial cancer (EC) tumor cells have been reported in several studies with inconsistent results. Furthermore, there is scarcity of data on the prevalence and prognostic significance of PD-L1 expression in EC from Middle Eastern ethnicity. We aimed to assess PD-L1 expression in a large cohort of Middle Eastern EC and to correlate this with clinico-pathological factors, as well as mismatch repair (MMR) protein status and patients’ outcome. PD-L1 expression was investigated using immunohistochemistry on tissue microarray in an unselected cohort of 440 EC. Kaplan–Meier and logistic regression analysis were used to compare the outcome and prognostic factors. PD-L1 expression in tumor tissue was detected in 18.9% (83/440) EC cases with no impact on survival. When stratified for MMR protein status, PD-L1 expression was similar for both MMR deficient and MMR proficient ECs. However, the expression of PD-L1 in tumor cells was significantly associated with type II (non-endometrioid) histology (p = 0.0005) and lymph node metastasis (p = 0.0172). Multivariate analysis showed PD-L1 expression to be an independent risk factor for lymph node metastasis (odds ratio: 2.94; 95% CI: 1.26–6.84; p = 0.0123). In conclusion, PD-L1 was strongly associated with non-endometrioid EC and was an independent prognostic marker of lymph node metastasis.